2023
DOI: 10.1002/tox.23853
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin suppresses angiotensin‐II‐enhanced oxidative stress and hypertrophic markers in H9c2 cells

Abstract: Myocardial hypertrophy plays a crucial role in cardiovascular disease (CVD) development. Myocardial hypertrophy is an adaptive response by myocardial cells to stress after cardiac injury to maintain cardiac output and function. Angiotensin II (Ang‐II) regulates CVD through the renin‐angiotensin‐aldosterone system, and its signaling in cardiac myocytes leads to excessive reactive oxygen species (ROS) production, oxidative stress, and inflammation. Sesamin (SA), a natural compound in sesame seeds, has anti‐infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Both systemic and local RAS act mutually in different tissues 32 . Importantly, the upregulation of AngII and activation of AT1 trigger the development of oxidative stress and inflammation by activating NADPH oxidase and inducing mitochondrial dysfunction 33 . Notably, NADPH oxidase is upregulated during the aging process and aging‐related disorders such as diabetes, hypertension, and atherosclerosis.…”
Section: A Brief Overview Of Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Both systemic and local RAS act mutually in different tissues 32 . Importantly, the upregulation of AngII and activation of AT1 trigger the development of oxidative stress and inflammation by activating NADPH oxidase and inducing mitochondrial dysfunction 33 . Notably, NADPH oxidase is upregulated during the aging process and aging‐related disorders such as diabetes, hypertension, and atherosclerosis.…”
Section: A Brief Overview Of Rasmentioning
confidence: 99%
“… 32 Importantly, the upregulation of AngII and activation of AT1 trigger the development of oxidative stress and inflammation by activating NADPH oxidase and inducing mitochondrial dysfunction. 33 Notably, NADPH oxidase is upregulated during the aging process and aging‐related disorders such as diabetes, hypertension, and atherosclerosis. However, stimulation of AT2 by AngII leads to an opposing effect characterized by inhibition of inflammation and oxidative stress mediated by AT1.…”
Section: A Brief Overview Of Rasmentioning
confidence: 99%
“… 29 Moreover, the RAS can induce paracrine and autocrine effects regardless of its systemic effects. 30 The harmful effect of AngII such as oxidative stress, mitochondrial dysfunction and inflammation is mediated through activation of NADPH oxidase. 26 It has been revealed that exaggerated NADPH oxidase activity and associated oxidative stress is linked with the development of age‐related disorders such as PD.…”
Section: Overview Of Rasmentioning
confidence: 99%
“…There has been recent interest in the ability of certain natural compounds to affect upstream signaling pathways that modulate the immune response, and hence potentially prevent cardiac hypertrophy. 10,11 The CTRP3 is a member of C1q/tumor necrosis factor (TNF)-related proteins and is widely expressed in different tissues, such as white adipose tissue, fibroblasts, chondrocytes, and monocytes. 12,13 It possesses multiple biological functions, such as regulating adipokine secretion, 14 promoting cell proliferation, 15 regulating hepatic lipid metabolism, 16 and inhibiting the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%